Genomic Characterization of Jumbo Salmonella Phages That Effectively Target United Kingdom Pig-Associated Salmonella Serotypes - Thanki, Anisha M.; Brown, Nathan; Millard, Andrew D.; Clokie, Martha R. J. (Frontiers in Microbiology, 2019)
A common cause of human food poisoning is through indigestion of pork products contaminated with Salmonella spp. Worryingly multi-drug resistant (MDR) Salmonella strains have been isolated from pigs, which motivates the need for alternative antimicrobials. In this study isolation and characterisation of 21 lytic Salmonella phages is described. All 21 phages, labelled as SPFM phages were shown to efficiently infect MDR Salmonella strains isolated from UK pigs and phages SPFM1, SPFM3, SPFM10, SPFM14, SPFM15, SPFM17 and SPFM19 could lyse 100% of strains tested. The phage genome sizes range from 233 Kb to 242 Kb, which qualifies them as jumbo phages. All SPFM phage genomes are approximately 95% similar to each other by average nucleotide identity, they encode between 258-307 coding sequences and share 188 core genes. Phylogenetic analysis shows these phages are most similar to phages of the genus Seoulvirus and to further characterise phages within the genus, genes under positive selection were identified. Several of the genes under evolutionary selection pressure were predicted to encode for proteins that interact with bacteria. We describe the phenotypic and genetic characterisation of this novel Salmonella phage set. As the phages efficiently kill MDR Salmonella strains, they may offer a promising alternative to antibiotics.